Effect of cationic polyamidoamine dendrimers on ionic transport through nanochannels. (20th January 2021) - Froehlich, Kristina; Ali, Mubarak; Ramirez, Patricio; Cervera, Javier; García-Morales, Vladimir; Erdmann, Markus; Ensinger, Wolfgang
Highlights: Nanochannels (conical and cylindrical) are fabricated via track-etch technique in polymer membrane. Immobilization of various cationic dendrimer generation on channels surface is achieved by carbodiimide coupling chemistry. Effect of surface charge density on the ion transport through single conical nanochannels is evaluated through I−V measurements. Dendrimer effect on mass transport is studied in multi-channel membranes through permeation experiments. Abstract: The effect of polyamidoamine (PAMAM) dendrimers (generations G0–G3) on the ion transport properties of nanochannels (conical and cylindrical) is studied either by surface functionalization or by addition to the electrolyte solution. Surface functionalization with cationic dendrimers lead to inversion of the ion current rectification, indicating the anion selectivity of the modified nanochannels. This anion selectivity increases by immobilizing higher-generation dendrimers, as expected for an increase in the surface density of amino groups. However, compared to PAMAM G2, functionalization with PAMAM G3 results in higher cation and lower anion fluxes. Diffusion experiments of charged analytes across nanochannel membranes confirm the effects of the dendrimers. Our experimental and theoretical results show that the observed effects are independent of the nanochannel geometry, but primarily relate to the average charge density and distribution of fixed charges on the channel surface. Graphical abstract: Image, graphical abstract